Kelayakan Investasi (Invesment Feasibility) Pembangunan Pasar Tradisional Rukoh Barona Kota Banda Aceh - Muhammad Arief; Nurul Malahayati; Buraida Buraida (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2019)
Rukoh Barona Market is a traditional market built and managed privately, is one of the container of economic resources of local people. It is located in Gampong Rukoh Utama District of Syiah Kuala City of Banda Aceh with a population of about 4,210 in habitants. Now the market with emergency buildings that use the private funds of this community, requires a proper rebuilding of the market. Aims to analyze the financial feasibility of traditional market development Rukoh Barona using personal capital is feasible or not to be done. The scope of this research is an investment feasibility analysis in the financial aspect of traditional market development design of Rukoh Barona. The research stage consists of designing 2 alternative images of buildings with semi-permanent and Permanent types, the calculation of the Cost Estimate (RAB) development and the analysis of Cash Flow. Cash Flow analysis methods use Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR) and Payback Period (PP) methods. Alternative NPV 1 Rp. 266.876.238,- and alternatives 2 Rp. 8.839.038,-, NPV 0 (feasible). Alternative IRR 1 = 18,4% and alternative 2 = 17,52%. Alternative BCR 1 = 1.9 and alternative 2 = 1.62, financially feasible and rewarding investment BCR ≥ 1. Alternative PP 1 capital back in 4 years 3 months and alternate 2 time 5 years 10 months. Both alternatives are feasible to do, but financially, the investment design of Traditional Market Rukoh Barona alternative 1 is better than alternative 2. Keywords: Market, Design, Cost Estimate, Invesment Feasibility, Financial Aspect.